2021
DOI: 10.1097/inf.0000000000003229
|View full text |Cite
|
Sign up to set email alerts
|

Is an Antenatal Screening for Chlamydia trachomatis Necessary in the Current Society?

Abstract: A screening of Chlamydia trachomatis infection in young pregnant women (≤25 years old) and their newborns was conducted. A total of 136 women were tested with urine samples in the immediate postpartum period. The prevalence was 18.4% (95% confidence interval [CI]: 11.9-24.9%) (25/136) and the rate of perinatal transmission was 35% (7/20). These results support the need for antenatal screening programs in high-risk women in Madrid (Spain).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Rours et al found screening of under‐30‐year‐old pregnant women to be cost‐effective, 33 and the prevalence in the 25–29 age group in our study suggest that screening in Gipuzkoa for pregnant women under 30 years old should be maintained, in line with recommendations of the Australian government 46 . In Spain, there have been studies focusing on under‐25‐year‐old pregnant women in Catalonia ( n = 599) and Madrid ( n = 136), found prevalence rates of 6.2% and 18.4% respectively, 48,49 although the sample size was small in the latter study. The prevalence of M. genitalium infection in our study was also higher among younger women, the rate in under‐25‐year‐olds (2.8%) being similar to that reported in France (2.4%) and Catalonia (2.5%), 38,48 and that in under‐20‐year‐olds (3.6%) being lower than that found in the United Kingdom (9%) 39 …”
Section: Discussionsupporting
confidence: 78%
“…Rours et al found screening of under‐30‐year‐old pregnant women to be cost‐effective, 33 and the prevalence in the 25–29 age group in our study suggest that screening in Gipuzkoa for pregnant women under 30 years old should be maintained, in line with recommendations of the Australian government 46 . In Spain, there have been studies focusing on under‐25‐year‐old pregnant women in Catalonia ( n = 599) and Madrid ( n = 136), found prevalence rates of 6.2% and 18.4% respectively, 48,49 although the sample size was small in the latter study. The prevalence of M. genitalium infection in our study was also higher among younger women, the rate in under‐25‐year‐olds (2.8%) being similar to that reported in France (2.4%) and Catalonia (2.5%), 38,48 and that in under‐20‐year‐olds (3.6%) being lower than that found in the United Kingdom (9%) 39 …”
Section: Discussionsupporting
confidence: 78%
“…The found prevalence of 7.43% of C. trachomatis is within the range of 6.15 to 16.7% in pregnant women in Brazil [6,15,24,39] and Botswana [40], lower than 11.2% in pregnant women in Latin America [23], 14.7% in Haiti [5] and 22.9% in Papua New Guinea [22]. When compared to developed countries such as France, with a prevalence of 2.5% [21], we have a considerably higher rate, but in European pregnant women under the age of 25, CT was found in 7.6% [21] and 18.4% [41], in France and Spain, respectively. Among women who have some risk factor for STI, we have a prevalence of 10.7% in Brazilian women under 25 years old [42], 2.1% in HIV-positive Brazilian women [43], 4% in Spanish women under 30 years old [11] and 9% in female sex workers [44], which was not found when we strati ed risk groups in our sample.…”
Section: Discussionmentioning
confidence: 68%
“…Another recent study highlighted a significant prevalence of Chlamydia trachomatis infections among young pregnant women below 25 years old, with an 18.4% infection rate and a 35% perinatal transmission rate. Therefore, the debate over the necessity of antenatal Chlamydia screening programs still remains [ 37 ]. Despite the demonstrated association between Chlamydia (and potentially Mycoplasma ) infection and preterm birth, the effectiveness and requirement of such screening programs in preventing adverse birth outcomes are subjects of ongoing discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the demonstrated association between Chlamydia (and potentially Mycoplasma ) infection and preterm birth, the effectiveness and requirement of such screening programs in preventing adverse birth outcomes are subjects of ongoing discussion. This controversy, as noted by Dorado CM et al [ 37 ], questions the universal application of these programs across different healthcare settings, especially when considering the varying success rates in several developed countries.…”
Section: Discussionmentioning
confidence: 99%